Unraveling Success in Online Learning: Exploring Helpfulness, Usefulness, Compatibility, and Satisfaction Among College Students in Chengdu, China - Chang, Liu (Scholar: Human Sciences, 2026)
Purpose: This study seeks to analyze the impact of online learning on 12 major universities in Chengdu, Sichuan Province, China. The primary research focuses on the helpfulness, perceived usefulness, compatibility, and satisfaction with online learning. Research design, data, and methodology: The sample data were gathered using a questionnaire survey. This study has a target population of 500 people. Before disseminating the questionnaire, the content's validity and reliability were assessed using Project Objective Consistency (IOC) and Cronbach's Alpha preliminary tests, with outstanding results. To examine the data, confirmatory factor analysis (CFA) and structural equation modeling (SEM) will be used to ensure the model's goodness of fit and confirm the causal relationship between the hypothesis testing variables. Results: Quality of experience significantly impacts helpfulness, and perceived ease of use significantly impacts perceived usefulness and compatibility. Product demonstrability was the strongest predictor of satisfaction, followed by product originality and perceived compatibility. Conclusion: Six of the eight hypotheses presented were supported and proved to achieve the research objectives. Therefore, developers should ensure the quality of experience, perceived ease of use, compatibility, product originality, and product demonstrability of online learning systems.